Soil Enzyme Activities, Organic Carbon and Microbial Population as Influenced by Integrated Nitrogen Management for Banana - and V.M. Amrutsagar, A.B. Jadhav, A.D. Kadlag (Journal of the Indian Society of Soil Science, 2016)
Soil enzyme activities, organic carbon (OC) and microbial population were assessed periodically in banana plantation imposed by integrated nitrogen (N) management treatments on Inceptisol during 2005-06. The treatment comprising substitution of N through farmyard manure (FYM), neem cake and vermicompost in 25, 50 and 33% proportion along with recommended dose of fertilizers (RDF). The OC content of soil was increased significantly by the application of inorganic fertilizers and organic manures viz., FYM, neem cake and vermicompost except the treatment received only RDF. The magnitude of increase in OC was significantly higher in the treatment receiving FYM, neem cake and vermicompost. The population of soil actinomycetes, bacteria and fungi were increased consistently up to 240 days after planting of banana. Higher population of actinomycetes (118×105 g-1 soil), fungal (141×104 g-1 soil) and bacteria (159×106 g-1 soil) were recorded with the application of organics. Soil urease and dehydrogenase activity was increased consistently up to 120 days after planting, whereas acid phosphatase activity increased up to 165 days after planting of banana. Significantly highest urease activity (44.8 mg NH4-N 100g-1 soil h-1) was obtained in soils receiving 50% N through FYM and 50% N through RDF followed by 100% N through FYM, vermicompost and neem cake (42.8 mg NH4-N 100g-1 soil h-1) at 120 days after planting, whereas significantly higher soil acid phosphatase activity (6.01 µMP g-1 soil h-1) and dehydrogenase activity (85.0 µg TPF g-1 soil 24h-1) were recorded with application of 100% N in equal proportion through FYM, neem cake and vermicompost. However, application of inorganic fertilizers as per soil test to banana resulted in lower magnitude of urease, acid phosphatase and dehydrogenase activity.